The Nuclear Equation of State in Heavy Ion Collisions - Gaitanos, T.; Colonna, M.; di Toro, M.; Wolter, H. H. (HNPS Advances in Nuclear Physics, 2020)
We present several possibilities offered by the dynamics of intermediate energy heavy ion collisions to investigate the nuclear matter equation of state (EoS) beyond the ground state. In particular the relation between the reaction dynamics and the high density nuclear EoS is discussed by comparing theoretical results with experiments.